In vitro exposure of porcine sperm to functionalized superparamagnetic nanoparticles - Garrappa, Gabriela; Martínez López, Cristina; Jiménez Movilla, María; García Vázquez, Francisco Alberto (Wiley, 2025)
Supplement: Proceedings of the 17th International Congress of the Spanish Society for Animal Reproduction (AERA), 17 to 19 of October 2024, Madrid, Spain